Implications and opportunities of precision medicine in rare malignancies. (1st September 2016) - Conley, Barbara A.; Sorg, Brian S.; Tricoli, James V.
ABSTRACT: Introduction : In aggregate, about 20% of all cancers can be considered rare. In addition, molecularly defined subsets of more common cancers are generally rare. Many rare cancers urgently need development of efficacious therapeutics, yet their rarity makes it difficult to conduct standard clinical trials. The advent of molecular profiling of cancers, however, may offer an opportunity for more thoughtful and successful development of new effective treatments. Areas covered : This manuscript describes instances in which drugs have been approved for rare cancers, and describes the potential value and challenges of new policies and research that may lead to more broad development of drugs based on the molecular characterization of a patient's tumor. Expert opinion : Although challenges in use of any methods for development of therapeutics for rare cancers exist, international collaboration, broad molecular profiling for research, and new trial designs such as basket designs and tumor agnostic designs, have promise to develop the evidence needed to assure that drugs will or will not be effective in rare cancers. Complimentary studies, such as those of exceptional responders, will add to the body of understanding that will hopefully lead to the discovery and development of effective treatments for many rare cancers.